(untitled) (Global Journal of Human-Social Science, 2024)
Aim of the article The purpose of the article is to define and analyze in the context of circology a unique feature in the World Circus Art namely Cirque du Soleil its doctrine and concept about the idea of the Blue Ocean in the context of producing the circus industry The relevance of the article lies in the fact that there are virtually no specific studies on this issue and topic In contemporary circology and domestic art criticism today there are no serious and deep scientific works Results The contemporary Cirque du Soleil is a unique circus structure of its kind among other circus structures and companies the International Circus Festival of Monte Carlo Monaco under the patronage of the Princely Grimaldi family dynastic circuses Krone in Munich Germany Knie in Zurich Switzerland Ronkalli traveling circus Germany as well as circus and performance show programs at the Friedrich Stadt Palace in Berlin Germany Capital Circus of Budapest F v rosi Nagycirkusz Hungary It is important to note that Cirque du Soleil is essentially a circus without the use of animals as well as its circus programs and shows which are held in different countries around the world and have a very large theatrical and acting component Cirque du Soleil is based in Montreal Canada Scientific novelty Uniqueness and novelty lies in identifying specific features and innovations in modern circus art in the context of its production and demonstration